High-safety high-entropy electrolyte, preparation method and battery

By using high-entropy electrolytes in sodium batteries, a solid electrolyte interface layer with high thermal stability is formed, which solves the flammability and explosive problem of traditional electrolytes under high temperature conditions, and achieves the high cycle life and safety of sodium batteries.

CN119764574AActive Publication Date: 2025-04-04SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411898188.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Traditional organic liquid electrolytes are flammable and explosive under high temperature conditions, and have poor thermal stability, which affects the circulation stability and safety of sodium batteries.

Method used

A high-safe high-entropy electrolyte is adopted, which consists of a variety of sodium salts and organic solvents to form an inorganic-rich and highly thermally stable solid electrolyte interface layer, and optimize the electrolyte components to improve thermal safety.

Benefits of technology

The electrochemical performance and thermal safety performance of sodium batteries are achieved, which significantly improves the cycle life and safety of the battery, reduces the temperature rise rate and heat accumulation during thermal runaway, and avoids serious combustion and explosion events.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764574A_ABST
    Figure CN119764574A_ABST
Patent Text Reader

Abstract

The invention relates to a high-safety high-entropy electrolyte, a preparation method and a battery, the high-entropy electrolyte is in a liquid state at room temperature and is composed of a sodium salt and an organic solvent, and the high-entropy electrolyte can form a solid electrolyte interface layer with high thermal stability on the surface of an electrode when the battery is normally charged and discharged. The high-entropy electrolyte is applied to the sodium battery, when the battery normally circulates, the high-entropy electrolyte can form a solid electrolyte interface layer with high thermal stability on the electrode side, the stable long cycle life of the battery is met, and meanwhile it can be guaranteed that the battery in the full charge state shows the low heat release rate and does not have the serious combustion explosion phenomenon under the thermal abuse condition; meanwhile, the high-entropy electrolyte can adapt to various sodium battery systems, and the normal operation requirement of a battery cell system prepared from the sodium battery is met. Besides, the preparation process of the high-entropy electrolyte is simple and convenient, the required raw materials are easy to obtain and low in cost, the long cycle life of the battery can be effectively realized, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytes and relates to a highly safe high-entropy electrolyte, a preparation method and a battery. Background Art

[0002] As a next-generation energy storage technology that is expected to replace lithium batteries, sodium batteries have received widespread attention in recent years. Compared with lithium resources, sodium resources are abundant and widely distributed, and have higher economy and sustainability. Therefore, sodium batteries have become an important candidate for future energy storage systems. As a key component of sodium batteries, electrolytes undertake core functions such as ion conduction, interface stability, and overall battery operation rate. However, traditional organic liquid electrolytes are flammable and explosive, and their thermal stability is poor. Under high temperature conditions, organic liquid electrolytes are prone to thermal decomposition, which in turn has an adverse effect on the cycle stability of the battery. In addition, the solid electrolyte interface layer formed by traditional organic liquid electrolytes on the electrode surface is usually rough, and it is easy to thermally decompose under high temperature conditions, causing the electrolyte to directly contact the sodium negative electrode and generate heat. At the same time, the release of reducing gases will further aggravate the exothermic reaction, greatly increasing the risk of thermal runaway of the battery, thereby endangering the safety and stability of the battery. It can be seen that the thermal safety of the electrolyte is an important factor in determining the overall performance of sodium batteries.

[0003] The researchers proposed a variety of solutions for how to achieve high-safety electrolytes for sodium batteries and their preparation methods and applications:

[0004] As shown in the literature (Angew.Chem.Int.Ed.2022,61,e202205045; J.Am.Chem.Soc.2024,146,15751.), high-concentration or locally high-concentration electrolytes increase the thermal decomposition temperature of the electrolyte, reduce the volatility and flammability of the electrolyte itself, and enhance the thermal safety of the electrolyte system. However, its viscosity and cost still need to be balanced, which hinders further practical energy storage applications.

[0005] For example, patent CN104900879B introduces phosphate solvents or flame retardant additives to achieve non-flammable electrolytes. However, this system improves the safety performance of sodium batteries at the expense of battery electrochemical performance.

[0006] For example, the literature (Chem. Eng. J. 2021, 425, 130612.) uses the excellent thermal stability, wide electrochemical window and low flammability of ionic liquid electrolytes to improve the safety and electrochemical performance of sodium batteries. However, its high viscosity and high cost are still the main obstacles to its widespread application.

[0007] Solid electrolytes are non-flammable and have excellent thermal stability. They can withstand high temperatures without decomposing, which significantly reduces the risk of fire and explosion. In addition, solid electrolytes can maintain excellent structural integrity under various harsh conditions. As shown in the literature (Adv. Energy Mater. 2017, 7, 1601196.), by designing solid electrolytes with high thermal stability and high mechanical strength, it is possible to minimize the occurrence of internal short circuits in the battery and other mechanical abuses that may cause thermal runaway. However, the poor electrode-electrolyte interface compatibility and low room temperature ionic conductivity of solid electrolytes have hindered the development and application of solid-state sodium batteries.

[0008] For example, the literature (J.Power Sources 2019, 423, 137; ACS Energy Lett. 2024, 9, 4111.; CN114156543A; CN113921907A, etc.) adds film-forming additives or adjusts the electrolyte formula to form a stable solid electrolyte interface layer on the electrode surface. A stable solid electrolyte interface layer is the key guarantee for the performance and safety of sodium batteries. It can effectively inhibit side reactions, delay battery degradation, and improve battery cycle stability and safety. However, traditional organic liquid electrolytes form a solid electrolyte interface layer rich in organic components on the electrode surface, which has poor thermal stability and is easily decomposed at high temperatures, resulting in a double decrease in battery cycle stability and safety. Therefore, how to optimize the electrolyte components to form a solid electrolyte interface layer with high thermal stability is an important research direction for achieving both electrochemical performance and safety of sodium batteries.

[0009] Recent studies have shown that the introduction of high-entropy electrolytes formed by multiple salt components can change the electrolyte solvation structure, thereby stabilizing the electrode-electrolyte interface phase. For example, the high-entropy electrolyte prepared in the literature (Adv. Mater. 2023, 35, 2210677.) significantly improves the cycle life and rate performance of the battery and is expected to expand high and low temperature applications. This study provides a new research idea for the design and development of the next generation of high energy density and high safety sodium batteries.

[0010] The high-entropy electrolyte system reported so far can significantly improve the electrochemical performance of the battery by virtue of the synergistic effect of multiple components. However, the high-entropy electrolyte components are complex and the interactions between the components are not yet clear. Under high temperature or extreme conditions, there may be pyrolysis behavior or adverse side reactions with electrode materials, which will affect the stability and safety of the battery and increase the risk of thermal runaway. Summary of the invention

[0011] The purpose of the present invention is to provide a high-entropy electrolyte with high safety, a preparation method and a battery, which can balance the electrochemical performance and thermal safety performance of sodium batteries.

[0012] The purpose of the present invention can be achieved by the following technical solutions:

[0013] In the first aspect, the present invention provides a highly safe high-entropy electrolyte, which is liquid at room temperature and consists of a sodium salt and an organic solvent. The high-entropy electrolyte contains solvated structure clusters involving multiple anions. During normal charging and discharging of the battery, such clusters preferentially decompose on the electrode surface due to their higher redox properties, forming a solid electrolyte interface layer that is rich in inorganic matter and has high thermal stability.

[0014] Furthermore, the organic solvent is two or more of propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and 1,3-dioxolane.

[0015] Further, the sodium salt is selected from any five or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalate borate, sodium bis(oxalate borate), sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, sodium nitrate, and sodium trifluoromethanesulfonate. Sodium salts known to be applicable to sodium ion battery electrolytes are collected. When a plurality of different types of sodium salts are combined in the electrolyte, the degree of disorder of the system can be significantly increased. When the entropy value reaches a certain value, this high entropy state can improve the chemical stability and thermodynamic stability of the electrolyte through the synergistic effect of multiple components, so that it can work stably under a wider temperature and voltage window, thereby avoiding unstable phenomena such as electrolyte decomposition and salt precipitation, and achieving multi-faceted battery performance.

[0016] Furthermore, the total concentration of the sodium salt in the high entropy electrolyte is 0.8-1.2 mol / L.

[0017] Furthermore, the different sodium salt components are added in equimolar amounts.

[0018] Furthermore, the water content in the high entropy electrolyte is less than 20 ppm.

[0019] In a second aspect, the present invention also provides a method for preparing a highly safe high-entropy electrolyte, wherein a sodium salt and an organic solvent are uniformly mixed under an inert atmosphere to obtain the high-entropy electrolyte.

[0020] In a third aspect, the present invention further provides a battery, wherein the battery uses a high-safety high-entropy electrolyte as described above as an electrolyte.

[0021] Furthermore, the battery is a sodium ion battery, a sodium metal battery or a negative electrode-free sodium battery.

[0022] Furthermore, in the battery cell system used in the battery, sodium nickel iron manganese oxide, sodium copper iron manganese oxide, sodium vanadium phosphate, sodium iron sulfate, sodium iron pyrophosphate or Prussian blue is used as the positive electrode material, there is no negative electrode, or one of hard carbon, soft carbon, titanium-based materials, alloy materials, metal oxides and sulfides, and sodium metal is used as the negative electrode material.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) The designed high entropy electrolyte is liquid at room temperature and has high ionic conductivity. The unique advantage of this application is that it can meet the normal charging and discharging requirements of sodium ion batteries, sodium metal full batteries and negative electrode-free sodium battery systems; in addition, the present invention well achieves a balance between the electrochemical performance and thermal safety performance of sodium batteries.

[0025] (2) Different from the traditional artificial solid-liquid interface layer, a solid electrolyte interface layer rich in inorganic components can be formed on the electrode surface in an electrolyte system containing multiple salt components, which is difficult to thermally decompose at high temperatures.

[0026] (3) The presence of the inorganic-rich solid electrolyte interface protective layer effectively increases the starting temperature of the sodium battery during thermal runaway, significantly reduces the temperature rise rate during thermal runaway, minimizes the heat accumulation of the sodium battery during thermal runaway, and alleviates the severity of thermal runaway of the sodium battery.

[0027] (4) Compared with existing electrolytes, the electrolyte in the present invention has a conventional concentration, low solvent components and sodium salt, low usage in the electrolyte, and no special requirements for the use environment.

[0028] (5) The electrolyte system can achieve a low heat release rate of the sodium battery during thermal runaway, ensuring the safe operation of the battery; the battery using the electrolyte system in this application has excellent room temperature long cycle performance, reliable safety performance, can reduce the temperature rise rate during thermal runaway, reduce the severity of thermal runaway events, and has no obvious combustion and explosion phenomena. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The cycle performance diagram of the sodium battery prepared by the high entropy electrolyte and the conventional electrolyte in Example 1;

[0030] Figure 2 This is an accelerated calorimetry test diagram of a fully charged sodium battery prepared with the high entropy electrolyte of Example 1;

[0031] Figure 3 This is a photo of a sodium battery prepared with a high entropy electrolyte in Example 1 after thermal runaway;

[0032] Figure 4The cycle performance diagram of the sodium battery prepared by the high entropy electrolyte of Example 1 and the electrolyte of Comparative Example 1;

[0033] Figure 5 This is an accelerated calorimetry test diagram of a fully charged sodium battery prepared using the electrolyte of Comparative Example 1;

[0034] Figure 6 The cycle performance diagram of the sodium battery prepared by the high entropy electrolyte of Example 1 and the electrolyte of Comparative Example 2; Figure 7 The cycling performance diagram of the sodium battery prepared with the high entropy electrolyte of Example 1 and the electrolyte of Comparative Example 3. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0036] In order to achieve a balance between electrochemical performance and thermal safety performance of sodium batteries, the present invention provides a high-safety high-entropy electrolyte, the preparation method of which is to uniformly mix any five or more sodium salts with an ester or ether organic solvent in an inert argon atmosphere.

[0037] In some specific embodiments, the organic solvent is composed of two or more of propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and 1,3-dioxolane.

[0038] In some specific embodiments, the sodium salt is any five or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium difluorooxalate borate, sodium bis(oxalate borate), sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, sodium nitrate, and sodium trifluoromethanesulfonate. Preferably, different sodium salts are added in equimolar amounts. In addition, the total concentration of all sodium salts is 0.8 to 1.2 mol / L, more preferably 1.0 mol / L.

[0039] The present invention can be further understood from the following examples, but the present invention is not limited to the following examples.

[0040] In the following examples, hard carbon, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was purchased from Shenzhen Kejing Zhida Technology Co., Ltd. The hard carbon model was Type 2 Kuraray, code 02009802; NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3The O2 model is MS-XN-33S, code 01009401. Figure 1 The conventional electrolyte was purchased from Duoduo Chemical Reagent Network with the item number NC-004. The formula is sodium perchlorate dissolved in ethylene carbonate / propylene carbonate with a volume ratio of 1:1 and 5% of fluoroethylene carbonate added to the total volume fraction. The electrolyte concentration is 1 mol / L.

[0041] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0042] Embodiment 1:

[0043] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the mixed electrolyte concentration was 1.0 mol / L. At room temperature, the electrolyte system was used to use hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The full battery test with O2 as the positive electrode found that the first cycle coulomb efficiency of the battery can reach 88.46%, the cycle life can reach 400 cycles, and the capacity retention rate is >80%. Figure 1 shown.

[0044] Figure 2 and Figure 3 It shows that when using an accelerating calorimeter (ARC) for thermal abuse testing, the starting temperature of thermal runaway of the sodium battery is 161.92°C, the temperature rise rate is low throughout the process, there are no serious fire and explosion incidents, and the safety performance is high.

[0045] Embodiment 2:

[0046] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, and sodium hexafluorophosphate. The concentration of each component was 0.2 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L. At room temperature, the electrolyte system was used to use hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as positive electrode

[0047] When using an accelerating rate calorimeter (ARC) for thermal abuse testing, the temperature rise rate of the sodium battery during thermal runaway is low, there are no serious fires or explosions, and the safety performance is high.

[0048] Embodiment 3:

[0049] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, and sodium nitrate. The concentration of each component was 0.143 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L. At room temperature, the electrolyte system was used to use hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as positive electrode

[0050] When using an accelerating rate calorimeter (ARC) for thermal abuse testing, the temperature rise rate of the sodium battery during thermal runaway is low, there are no serious fires or explosions, and the safety performance is high.

[0051] Embodiment 4:

[0052] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of eight kinds of sodium salts: sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, sodium nitrate, and sodium trifluoromethanesulfonate. The concentration of each component was 0.125 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L. At room temperature, the electrolyte system was used to use hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as positive electrode

[0053] When using an accelerating rate calorimeter (ARC) for thermal abuse testing, the temperature rise rate of the sodium battery during thermal runaway is low, there are no serious fires or explosions, and the safety performance is high.

[0054] Embodiment 5:

[0055] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, sodium nitrate, sodium trifluoromethanesulfonate, and sodium bis(oxalatoborate). The concentration of each component was 0.111 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0056] The electrolyte system is used for hard carbon as negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as positive electrode

[0057] Embodiment 6:

[0058] A mixed solution of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate with a volume ratio of 1:1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0059] The electrolyte system is used for hard carbon as negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as positive electrode

[0060] Embodiment 7:

[0061] A mixed solution of ethylene glycol dimethyl ether / ethylene glycol diethyl ether / 1,3-dioxolane with a volume ratio of 1:1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0062] The electrolyte system is used for hard carbon as negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full battery test with O2 as the positive electrode. Example 8:

[0063] A mixed solution of trimethyl phosphate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0064] The electrolyte system was used for full battery testing with hard carbon as the negative electrode and sodium vanadium phosphate as the positive electrode.

[0065] Embodiment 9:

[0066] A mixed solution of propylene carbonate / ethylene glycol dimethyl ether / fluoroethylene carbonate with a volume ratio of 1:1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0067] The electrolyte system was used for full-cell testing with hard carbon as the negative electrode and sodium iron pyrophosphate as the positive electrode.

[0068] Embodiment 10:

[0069] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether / fluoroethylene carbonate with a volume ratio of 1:1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0070] The electrolyte system was used for full battery testing with hard carbon as the negative electrode and Prussian blue analogue as the positive electrode.

[0071] Embodiment 11:

[0072] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0073] The electrolyte system is used for soft carbon as negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full cell test with O2 as the positive electrode.

[0074] Embodiment 12:

[0075] A mixed solution of propylene carbonate / ethylene carbonate / fluoroethylene carbonate with a volume ratio of 1:1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0076] The electrolyte system was used for full battery testing with Na2Ti3O7 as the negative electrode and sodium vanadium phosphate as the positive electrode.

[0077] Embodiment 13:

[0078] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0079] The electrolyte system is used for red phosphorus or black phosphorus as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full cell test with O2 as the positive electrode.

[0080] Embodiment 14:

[0081] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0082] The electrolyte system is used for sodium metal as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full cell test with O2 as the positive electrode.

[0083] Embodiment 15:

[0084] A mixed solution of ethylene carbonate / ethylene glycol dimethyl ether with a volume ratio of 1:1 was prepared. The sodium salt was a mixture of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, and sodium perchlorate. The concentration of each component was 0.167 mol / L, and the total concentration of the mixed electrolyte was 1.0 mol / L.

[0085] The electrolyte system was used for the copper foil as the negative electrode current collector, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Full cell test with O2 as the positive electrode.

[0086] Through Examples 1-15, it can be seen that when a sodium battery using a high-entropy electrolyte is cycled normally, a solid electrolyte interface layer rich in inorganic components and with high thermal stability is formed on the electrode surface, which ensures the electrochemical properties of the sodium battery, such as a long cycle life. At the same time, during the thermal runaway process, the decomposition temperature of the electrode-electrolyte interface layer is significantly increased, the temperature rise rate throughout the thermal runaway process is reduced, heat accumulation is reduced, there are no serious combustion and explosion incidents, and the safety performance is high.

[0087] Comparative Example 1:

[0088] Compared with Example 1, most of the above are the same, except that the sodium salt is replaced by a single sodium perchlorate with an equimolar total amount, and the electrolyte concentration is 1.0 mol / L. This electrolyte system is used for hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The full battery test with O2 as the positive electrode found that the capacity retention rate dropped below 80% after 150 cycles. Figure 4 shown.

[0089] When using an accelerating calorimeter (ARC) for thermal abuse testing, the thermal runaway starting temperature of the sodium battery is 52.386°C, the temperature rise rate is high throughout the process, and the safety is poor. Figure 5 .

[0090] Comparative Example 2:

[0091] Compared with Example 1, most of the contents are the same, except that the concentration of sodium perchlorate is increased to 0.5 mol / L, and the other five salts are all 0.1 mol / L, and the total electrolyte concentration is 1.0 mol / L. 1 / 3 Fe 1 / 3 Mn 1 / 3 The full battery test with O2 as the positive electrode found that the capacity retention rate dropped below 80% after 60 cycles. Figure 6 shown.

[0092] Comparative Example 3:

[0093] Compared with Example 1, most of the above are the same, except that the organic solvent system is replaced by a single organic solvent, ethylene glycol dimethyl ether, and the electrolyte concentration is 1.0 mol / L. This electrolyte system is used to use hard carbon as the negative electrode, NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 The full battery test with O2 as the positive electrode found that the capacity retention rate dropped below 80% after 50 cycles. Figure 7 shown.

[0094] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A highly safe high entropy electrolyte, characterized in that: It is liquid at room temperature and is composed of a variety of sodium salts and organic solvents. The high entropy electrolyte can form a solid electrolyte interface layer that is rich in inorganic matter and has high thermal stability when the battery is normally charged and discharged.

2. A highly safe high entropy electrolyte according to claim 1, characterized in that: The organic solvent is two or more of propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and 1,3-dioxolane.

3. A highly safe high entropy electrolyte according to claim 1, characterized in that: The sodium salt is selected from any five or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, sodium bis(oxalatoborate), sodium tetrafluoroborate, sodium hexafluorophosphate, sodium perchlorate, sodium nitrate, and sodium trifluoromethanesulfonate.

4. A highly safe high entropy electrolyte according to claim 3, characterized in that: The concentration of the sodium salt in the high entropy electrolyte is 0.8-1.2 mol / L.

5. A highly safe high entropy electrolyte according to claim 3, characterized in that: The different sodium salt components were added in equimolar amounts.

6. A highly safe high entropy electrolyte according to claim 1, characterized in that: The water content in the high entropy electrolyte is less than 20 ppm.

7. A method for preparing a high-safety high-entropy electrolyte according to any one of claims 1 to 6, characterized in that: Under an inert atmosphere, the sodium salt and the organic solvent are mixed evenly to obtain the high entropy electrolyte.

8. A battery, characterized in that: The battery uses a high-safety high-entropy electrolyte as described in any one of claims 1 to 5 as an electrolyte.

9. The battery according to claim 8, characterized in that The battery is a sodium ion battery, a sodium metal battery or a negative electrode-free sodium battery.

10. The battery according to claim 8, characterized in that In the battery cell system used in the battery, sodium nickel iron manganese oxide, sodium copper iron manganese oxide, sodium vanadium phosphate, sodium iron sulfate, sodium iron pyrophosphate or Prussian blue is used as the positive electrode material, there is no negative electrode, or one of hard carbon, soft carbon, titanium-based materials, alloy materials, metal oxides and sulfides, and sodium metal is used as the negative electrode material.

Citation Information

Patent Citations

  • Non-aqueous high-entropy electrolyte and lithium ion battery

    CN117254116A

  • Sodium-ion battery electrolyte as well as preparation method and application thereof

    CN118659036A

  • Electrolytes for Low Temperature Applications

    US20220140398A1

  • High entropy liquid electrolytes for li-ion or na-ion batteries

    WO2024123177A1